ANALISIS RANTAI PASOK CRUDE PALM OIL (CPO) DI KABUPATEN PASAMAN BARAT - Lisa Nesti; Tan, Firwan; Hadiguna, Rika (Agripita Publisher, 2017)
ABSTRACT . In accordance with today's economic globalization, supply chain management of agribusiness and agroindustry in developing countries, especially Indonesia should be critically examined in managing the flow of products and services along with the value added chain of agricultural and food products to embody the higher customer value at an affordable price level. Agro commodities are included into strategic commodities for the crucial roles because of they are provided primary needs, embodied the additional national values, to provide workplaces, to develop industrial division, to transfer technology and increase the result of the foreign exchange. Crude Palm Oil (CPO) is a product processed from palm oil that is still an excellent commodity in West Pasaman which has a tendency to increase production from year to year. The purpose of this study is to get an overview of CPO supply chain in West Pasaman by reviewing all activities covering the flow of goods, information flow and cash flow that occurs in the supply chain. The results showed that in the flow of goods, there are three forms of the flow of supplies palm fruits to Agro Industries are distinguished by palm fruits of independent smallholders, farmers and palm fruits from the nucleus, while the flow of information includes feedback information received and given by each supply chain actors CPO include farmers, mill palm oil processing, expedition CPO, CPO mill and factory CPO refinery dan export while the cash flow coming from downstream (end consumer) to the upstream in the form of price realization of commodities purchase and sale agreement in the supply chain. ABSTRAK. Sejalan dengan globalisasi ekonomi saat ini, manajemen rantai pasokan agribisnis dan agroindustri di negara berkembang khususnya Indonesia harus dicermati secara kritis dalam mengelola aliran produk dan jasa sepanjang rantai nilai tambah produk pertanian dan pangan dalam upaya mewujudkan nilai konsumen yang unggul pada tingkat harga yang terjangkau. Beberapa komoditi Agro merupakan komoditas strategis karena perannya yang sangat besar bagi masyarakat sebagai penyedia kebutuhan pokok masyarakat, menciptakan nilai tambah di dalam negri, penyerapan tenaga kerja, pengembangan wilayah industri, proses alih teknologi dan sebagai hasil devisa negara. Crude Palm Oil (CPO) merupakan produk olahan dari kelapa sawit yang saat ini masih menjadi komoditi primadona di Kabupaten Pasaman Barat yang memiliki kecenderungan peningkatan produksi dari tahun ketahun. Tujuan penelitian ini adalah mendapatkan gambaran rantai pasok CPO di Kabupaten Pasaman Barat dengan mengkaji seluruh aktifitas yang mencakup aliran barang, aliran informasi dan aliran uang yang terjadi pada rantai pasok tersebut. Hasil penelitian menunjukkan bahwa pada aliran barang, terdapat tiga bentuk aliran pasokan TBS ke Agro Industri yang dibedakan berdasarkan TBS dari petani swadaya, petani plasma dan TBS dari kebun inti, sedangkan aliran informasi mencakup informasi timbal balik yang diterima dan diberikan oleh masing-masing pelaku rantai pasok CPO mencakup petani, pabrik pengolahan kelapa sawit, ekspedisi CPO, pabrik pengolahan CPO, pabrik refinery CPO dan ekspor, sedangkan aliran uang berasal dari hilir (konsumen akhir) sampai ke hulu dalam bentuk realisasi harga dari kesepakatan jual beli komodi dalam rantai pasok tersebut.